Integrated multitrophic aquaculture systems: potential risks for food safety - Rosa, João (2020)
Background: The demand for fish and fish products is now higher than ever. However, several problems such as nutrient loading or excessive use of resources can be associated with the intensification of aquaculture systems. Integrated multitrophic aquaculture systems (IMTAs) refer to the co-culture of different species belonging to different trophic levels, and offer a sustainable approach to aquaculture development. In these systems, organic and inorganic extractive species will feed on other species waste or on uneaten feed nutrients, acting as bioremediators. Scope and approach: The extractive capacity that these organisms have to take up nutrients from the water also means they will accumulate chemicals that are often administered in intensive productions. The present review describes a vast number of substances that can be found in IMTAs, either intentionally administered or resulting from contamination, and subsequently accumulated in species reared afterwards in these systems. The presence of such chemicals in organisms produced in IMTAs raises several food safety and human health concerns, which need to be addressed. Key findings and conclusions: Although IMTAs still face many challenges in terms of large scale production, legislations are not yet ready to comprise co-cultivation of multiple species in proximity. Also, maximum residue limits already existent for fish must be set for other organisms also produced in IMTAs in order to protect consumer's health. An increase in extractive species consumption (e.g. seaweeds) has been noticed during the past few years, and as IMTAs gain importance as a sustainable production method, food safety issues must be tackled.